English writing in blogs: analyses of preservice teachers’ versions of Sad I Ams - Kee, Li Li; Razali, Abu Bakar (Institut Pendidikan Guru Kampus Pulau Pinang, 2019)
English writing is important to be promoted among pre-service teachers who will teach writing skill to the students and they are still lacking in it. The use of blogs is also known to be able to ignite the change in the learning of English writing. Hence, this study explored the use of blogs to improve English writing among pre-service teachers. The research adopted a qualitative research design conducted using document analysis technique on six pre-service teachers’ written poems. Through the idea of social constructivism, the researcher/lecturer modelled the process of composing a version of “Sad I Ams” while the participants composed their versions of “Sad I Ams” as blog entries. The use of blogs was found to improve the English writing among the participants from their improved content, communicative achievement, organisation and language domains. The researchers believed that the use of blogs should be carried out over a longer duration to develop English writing with the suggestion of a more interactive blog usage.